2013
DOI: 10.1007/s10461-013-0535-8
|View full text |Cite
|
Sign up to set email alerts
|

Test of a Web-Based Program to Improve Adherence to HIV Medications

Abstract: We evaluated the effectiveness of a web-based version of the Life-Steps intervention combined with modules for stress reduction and mood management, designed to improve medication adherence among HIV infected individuals. 168 HIV+ adults were randomized into either the Life-Steps program or a waitlist control condition. All participants completed a baseline assessment and provided a 2-week electronic pill (MEMS) cap baseline reading. Follow up data collection was conducted at 3, 6 and 9 months. Patients in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 36 publications
2
55
1
Order By: Relevance
“…79 The country in which the study was conducted was not reported in five studies. [80][81][82][83][84] The median sample size was 170 (min = 34; max 966).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…79 The country in which the study was conducted was not reported in five studies. [80][81][82][83][84] The median sample size was 170 (min = 34; max 966).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The effects of interventions are summarized in Table 1 46,48,54,62,64,[66][67][68]73,81 Details of the latter studies serve to illuminate the most potent interventions among the studies in this review. Chung and colleagues 66 conducted a randomized controlled factorial design trial in 361 treatment naïve HIV-infected adults in Nairobi, Kenya initiating ART.…”
Section: Effects Of Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive Health Check (PHC) is a web-based video counseling tool to reduce HIV transmission and improve health outcomes for people living with HIV (PLWH). The tool was developed based on evidence that computer-based counseling tools can reduce sexual risk behaviors and improve antiretroviral therapy (ART) adherence [1,2,[10][11][12][13] and viral load suppression [12]. PHC is grounded in the Information-BehaviorMotivation model [14], Motivational Interviewing [15], and the Transtheoretical model [16].…”
Section: Introductionmentioning
confidence: 99%